Henoch-Schonlein purpura associated with HLA-B27 positive axial spondyloarthritis in a young man. Issue 5 (24th May 2019) - John, Kevin John; Sadiq, Mohammad; Thomas, Meera; Turaka, Vijay Prakash
Abstract : Axial spondyloarthropathies are characterised by bilateral sacroiliitis, asymmetric oligoarthritis, association with the human leucocyte antigen (HLA)-B27, enthesitis and dactylitis. Although IgA nephropathy has a well-documented association with seronegative spondyloarthropathies, the association with Henoch-Schonlein purpura (HSP) has been documented only in few case reports. The present case is that of a 26-year-old man who presented with fever, lower limb arthritis, abdominal pain, palpable purpura over the buttocks and lower limbs, and clinical features of sacroiliitis. His blood tests showed elevated inflammatory markers and rheumatoid factor was negative. CT scan of the sacroiliac joints confirmed sacroiliitis. Skin biopsy revealed neutrophilic small vessel vasculitis. HLA-B27 was positive in blood. A diagnosis of HSP with HLA-B27 positive axial spondyloarthritis was made. HSP can be associated with HLA-B27 positive axial spondyloarthritis and has to be considered while evaluating for causes of cutaneous small vessel vasculitis in such patients.